Farmers' knowledge of tree attributes and shade canopy management of cocoa agroforestry systems in Waslala, Nicaragua - Silva Aguad, Claudia P. (2013)
Project submitted in partial fulfilment of the requirements for the degree of Master of Science (MSc) in Agroforestry